Consumption Smoothing and Excess Female Mortality in Rural India - Rose, Elaina (The Review of Economics and Statistics, 1999)
This paper examines the relationship between consumption smoothing and excess female mortality, by asking if favorable rainfall shocks in childhood increase the survival probabilities of girls to a greater extent than they increase boys' survival probabilities for a sample of rural Indian children. In order to avert the issue of selection bias due to underreporting of births of girls, a methodology is employed that does not require data on births by gender. The results indicate that favorable rainfall shocks increase the ratio of the probability that a girl survives to the probability that a boy survives.